Famiglie migranti e mediazione interculturale: Il ruolo delle strutture ecclesiali - Grazioli, Orietta Rachele (Vergentis, 2020)
The contribution, starting from the examination of the canonical sources, aims to analyze the migratory phenomenon from the point of view of family relationships, which are modified and separated due to migration and pose considerable questions of managing the mutual bonds and regeneration of the same. In this context, not only the dynamics of migrant families with the host area are dealt with, but also the intra-family relationships with the second and third generations, born, educated and raised in the host country. From the point of view of helping families, the role of ecclesial structures must therefore be able to be characterized today also by the attention paid to the management of internal and external conflict dynamics with a view to intercultural and intergenerational family mediation, in order to enhance the human and personal wealth that the comparison between diversity favors. Finally, the work considers a concretization of the attention to the migratory phenomenon, in the experience lived in the Diocese of Milan with the celebration of the Minor Synod for the Ambrosian Church with the theme "Church from the People".